Molybdenum(VI) bis-imido Complexes of Dipyrromethene Ligands - Locher, Jan; Watt, Fabian A.; Neuba, Adam G.; Schoch, Roland; Munz, Dominik; Hohloch, Stephan (Inorganic Chemistry, 2020)
We report the synthesis of high-valent molybdenum(VI) bis-imido complexes 1-4 with dipyrromethene (DPM) supporting ligands of the general formula (DPMR)Mo(NR′)2Cl (R, R′ = mesityl (Mes) or tert-butyl (tBu)). The electrochemical and chemical properties of 1-4 reveal unexpected ligand noninnocence and reactivity. 15N NMR spectroscopy is used to assess the electronic properties of the imido ligands in the tert-butyl complexes 1 and 3. Complex 1 is inert toward ligand (halide) exchange with bulky phenolates such as KOMes or amides (e.g., KN(SiMe3)2), whereas the use of the lithium alkyl LiCH2SiMe3 results in a rare nucleophilic β-alkylation of the DPM ligand. While the reductions of the complexes occur at molybdenum, the oxidation is centered at the DPM ligand. Quantum-chemical calculations (complete active space self-consistent field, density functional theory) suggest facile (near-infrared) interligand charge transfer to the imido ligand, which might preclude the isolation of the oxidized complex [1]+ in the experiment.
CRIS-Team Scopus Importer:2020-07-24